EFEKTIVITAS PEMBELAJARAN PAI MELALUI PENERAPAN METODE MAKE A MATCH DI SMAN 6 KARAWANG - Tiara Safitri Tiara; Siti Masruroh; Mitra Sasmita (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
This research identifies the gap between conventional teaching methods applied by Islamic Religious Education (PAI) teachers in class XI at SMAN 6 Karawang and the demands of modern learning that emphasize student engagement. The purpose of the research is to determine and analyze the effectiveness of the Make a Match method in improving students' understanding and activity in PAI learning, as well as comparing the differences with traditional teaching methods. A qualitative research approach was used, with data collection through direct observation of the learning process to record student-teacher interactions and group dynamics, in-depth interviews with teachers and students, and analysis of documentation such as lesson plans and class notes. The research results show that the application of the Make a Match method in class X resulted in significant improvements, where students appeared more active, engaged, and enthusiastic compared to class XI, which used conventional methods. These findings confirm that the selection of innovative learning methods that suit student characteristics greatly influences the effectiveness of PAI learning. Based on these results, this research recommends that teachers implement interactive methods like Make a Match to optimize the quality of the teaching and learning process at the high school level.